Facilitation of Intensive Insulin Therapy in the Early Primary School Setting: Narratives of Australian Diabetes Educators. Issue 3 (3rd July 2018) - Marks, Anne; Wilson, Nathan J.; Blythe, Stacy; Johnston, Christine
ABSTRACT: The number of early primary school (EPS) children (aged 4–8 years) with type 1 diabetes mellitus (T1DM) rises each year. Intensive insulin therapy (IIT) can be challenging for these children, as adult support may not be available in the school setting. Diabetes educators (DEs) working in the health system facilitate school diabetes care, which can be time-consuming given the large numbers of children with diabetes. These factors are potential barriers for IIT use in the EPS setting. To explore the experiences of Australian DEs who facilitate IIT use in the EPS setting, a qualitative, narrative inquiry method was used to conduct semi-structured telephone interviews with Australian DEs ( n = 13) between December 2014 and June 2016. The interview transcript data were analyzed using a narrative analytical approach. Approaches to facilitate IIT use in the EPS setting were normalizing IIT at diagnosis, simple care plans and insulin pump therapy, prioritizing school support, DEs in private practice, and working with school nurses and parents. Despite numerous barriers, Australian DEs implemented varied methods to facilitate IIT use in the EPS setting.